Early Onset Asthma, But Not Aeroallergen Sensitization, Is Associated With Lung Function Impairment in Young Adulthood—A Prospective Cohort Study - Joakim Bunne; Linnea Hedman; Anders Bjerg; Matthew Perzanowski; Thomas Platts‐Mills; Eva Rönmark (Clinical and Translational Allergy)
ABSTRACT Background Aeroallergen sensitization is a major factor in asthma, and asthma is associated with impaired lung function. The independent association between sensitization and lung function is unclear. Objectives To examine factors associated with lung function in adolescence, with special interests in sensitization and asthma. Methods All schoolchildren in grade one and two (median age 8) in two municipalities in Northern Sweden were invited to a questionnaire survey of allergic diseases and skin prick tests to aeroallergens. This was repeated at ages 12 and, at 19 years also including spirometry and n = 1495 participated at all three occasions. Associations between risk factors and FEV1, FVC and FEV1/FVC were analysed by linear regression. Results Aeroallergen sensitization was not associated with lung function, irrespective of age at onset, type or degree of sensitization. Early‐onset asthma, both persistent (B −0.35, 95% CI –0.60 to −0.09) and in remission (B −0.43, 95% CI –0.74 to −0.12) was associated with lower FEV1. Persistent asthma was associated with lower FEV1/FVC (B −0.81, 95% CI –1.07 to −0.55), and remission with lower FVC (B −0.37, 95% CI –0.67 to −0.70). No interaction between asthma and sensitization was found. Maternal smoking in pregnancy was associated with lower FEV1/FVC. Underweight at age 19 years was associated with lower FEV1 and FVC and overweight was associated with higher FEV1 and FVC, but lower FEV1/FVC. Conclusions Aeroallergen sensitization was not independently associated with lung function. Early onset asthma was strongly associated with lung function impairments in young adulthood and in sensitized and non‐sensitized individuals alike.